Antifungal Activity of Phenolic Compounds From Samanea Saman Leaves Against Stem Rot Disease on Dragon Fruits Caused by Fusarium Solani - Rita, Wiwik Susanah; Suprapta, Dewa Ngurah; Swantara, I Made Dira; Sudana, I Made (KnE Life Sciences, 2022)
Fusarium solani is a pathogen that causes dragon fruit stem rot. Phenolic compounds are thought to slow the progression of the disease. The aim of this research was to determine the quantity of phenolic compounds in Samanea saman leaf extract, identify the phenolic compounds, and evaluate their antifungal activity against F. solani. Extraction was done by maceration with 96% ethanol, followed by fractionation. Total phenolic content was determined by UV-Vis spectroscopy. Purification was performed by chromatographic technique. The isolate was identified by phytochemical test and spectroscopy technique. Antifungal assay was carried out by well diffusion agar. The total phenolic content of the acetone extract was 6589.12 mg GAE/100g extract. The extract strongly inhibited the growth of the pathogenic fungi with an inhibitory zone of 25.50 mm. The active isolate strongly inhibited the growth of F. solani with an inhibition zone of 35.50 mm. The phytochemical test and UV-Vis spectroscopy analysis showed that the isolate was hydrolyzed tannin, which absorbs ultraviolet light with a wavelength of 264.90 nm. The infrared spectroscopy analysis showed that the functional groups of tannin are OH (phenol), -CH aliphatic, -C=O, -C=C aromatic, and -CO. Keywords: Antifungal activity, Dragon Fruit, Phenolic compounds, Samanea sama